2019
DOI: 10.35940/ijitee.a1013.0881019
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things Based Early Detection of Diabetes Using Machine Learning Algorithms: Dpa

Abstract: This paper introduces a new decision tree algorithm Diabetes Prediction Algorithm (DPA), for the early prediction of diabetes based on the datasets. The datasets are collected by using Internet of Things (IOT) Diabetes Sensors, comprises of 15000 records, out of which 11250 records are used for training purpose and 3750 are used for testing purpose. The proposed algorithm DPA yielded an accuracy of 90.02 %, specificity of 92.60 %, and precision of 89.17% and error rate of 9.98%. further, the proposed algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…• Rely on manual labeling by doctors which is timeconsuming and laborious 10 . Therefore, in response to the aforementioned issues, several researchers have proposed implementing computer-aided diagnosis, which can simplify the work of physicians and decrease the likelihood of misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Rely on manual labeling by doctors which is timeconsuming and laborious 10 . Therefore, in response to the aforementioned issues, several researchers have proposed implementing computer-aided diagnosis, which can simplify the work of physicians and decrease the likelihood of misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in response to the aforementioned issues, several researchers have proposed implementing computer-aided diagnosis, which can simplify the work of physicians and decrease the likelihood of misdiagnosis. Previous research on various CDs [4][5][6][7][8][9][10][11] has demonstrated that it is feasible to detect and categorize CDs using Machine Learning (ML) technology. However, such approaches have shown lower performances and exhibit some limitations such as imbalanced data, accuracy paradox, missing data problems, slow convergence by metaheuristic techniques like Genetic Algorithm (GA), etc.…”
Section: Introductionmentioning
confidence: 99%